Hayek, Mill and the Liberal Tradition - Farrant, Andrew (Routledge Studies in the History of Economics, 2010)
This book considers the relationship between Hayek and Mill, taking issues with Hayek's criticism of Mill and providing a broader perspective of the liberal tradition. Featuring contributions from the likes of Ross Emmett, Leon Montes and Robert Garnett, these chapters ask whether Hayek had an accurate reading of the ideas of Mill and Smith, as well as considering themes such as sympathy and analytical egalitarianism that play a large part in the liberal tradition, but less in work of Hayek These chapters argue that addition of these key ideas to the Hayekian corpus leads to a far broader understanding of the liberal tradition than that provided by Hayek Introduction, Andrew Farrant , 1.Hayek and the Liberal Tradition, 1. Is Friedrich Hayek rowing Adam Smith's boat, Leon Montes , 2. F. A. Hayek's Sympathetic Agents, David M. Levy and Sandra Peart , 3. Discussion and the Evolution of Institutions in a Liberal Democracy: Frank Knight Joins the Debate, Ross Emmett , 2. Pushing the Boundaries of the Liberal Tradition? , 4. Hayek, Mill, and the Problem of Institutional Change?, Andrew Farrant , 5. A Socialist Spontaneous Order, Theodore A. Burczak , 6. Hayek and Philanthropy: A Classical Liberal Road Not (Yet) Taken, Robert Garnett